Amelioration of Obesity-Related Disorders in High-Fat Diet-Fed Mice following Fecal Microbiota Transplantation from Inulin-Dosed Mice - Yinli Huang; Na Ying; Qihui Zhao; Junli Chen; Sin-Yeang Teow; Wei Dong; Minjie Lin; Lingling Jiang; Hong Zheng (Molecules, 2023)
The role of inulin in alleviating obesity-related disorders has been documented; yet, its underlying mechanisms still need to be further investigated. This study attempted to elucidate the causative link between the gut microbiota and the beneficial effect of inulin on obesity-related disorders via transferring the fecal microbiota from inulin-dosed mice to high-fat diet (HFD)-induced obese recipient mice. The results show that inulin supplementation can decrease body weight, fat accumulation, and systemic inflammation and can also enhance glucose metabolism in HFD-induced obese mice. Treatment with inulin reshaped the structure and composition of the gut microbiota in HFD-induced obese mice, as characterized by increases in the relative abundances of Bifidobacterium and Muribaculum and decreases in unidentified_Lachnospiraceae and Lachnoclostridium. In addition, we found that these favorable effects of inulin could be partially transferable by fecal microbiota transplantation, and Bifidobacterium and Muribaculum might be the key bacterial genera. Therefore, our results suggest that inulin ameliorates obesity-related disorders by targeting the gut microbiota.